2015
DOI: 10.1002/2014jb011763
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal distribution of deformation at the front of the Andean orogenic wedge in southern Bolivia

Abstract: New observations from an active orogenic wedge help link the seismotectonic behavior of individual faults to wedge deformation rates and patterns over multiple timescales. We provide the first detailed constraints on the distribution and timing of deformation at the front of the Andean orogenic wedge in southern Bolivia, where a recent study suggests that great (M w > 8) earthquakes could rupture the master fault underlying the wedge. We use stratigraphic relationships across fault-related folds and elastic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 113 publications
2
33
0
Order By: Relevance
“…This is in contrast to the Bolivian sector of the foreland, between 17.5°S and 22°S, where Horton (1999) combined GPS data with estimates for long-term erosion rates in the Subandes to demonstrate that the orogenic wedge at those latitudes is likely critically tapered. The findings of Horton (1999) are consistent with the observation that the geodetically derived values for slip rate on the décollement in Bolivia agree well with geologically determined rates and that almost all of the Quaternary deformation there is being accommodated on structures near the thrust front (Weiss et al, 2016;Weiss et al, 2015). Although the geodetically derived dislocation model for the décollement reported here for the Santa Barbara system is similar to that inferred by Brooks et al (2011) and Weiss et al (2016) for the Bolivian section, we suspect that the inferred slip is not fully transmitted to the wedge front in our study area and therefore not recorded in the geologic slip rates on the thrust front at Lomas de Olmedo.…”
Section: Comparison Of Geodetically Derived Décollement Parameters Wisupporting
confidence: 83%
“…This is in contrast to the Bolivian sector of the foreland, between 17.5°S and 22°S, where Horton (1999) combined GPS data with estimates for long-term erosion rates in the Subandes to demonstrate that the orogenic wedge at those latitudes is likely critically tapered. The findings of Horton (1999) are consistent with the observation that the geodetically derived values for slip rate on the décollement in Bolivia agree well with geologically determined rates and that almost all of the Quaternary deformation there is being accommodated on structures near the thrust front (Weiss et al, 2016;Weiss et al, 2015). Although the geodetically derived dislocation model for the décollement reported here for the Santa Barbara system is similar to that inferred by Brooks et al (2011) and Weiss et al (2016) for the Bolivian section, we suspect that the inferred slip is not fully transmitted to the wedge front in our study area and therefore not recorded in the geologic slip rates on the thrust front at Lomas de Olmedo.…”
Section: Comparison Of Geodetically Derived Décollement Parameters Wisupporting
confidence: 83%
“…Analogue and numerical models have shown that wedges evolve via distinct phases of widening, when new thrusts nucleate at the front of the wedge, and (Figure 11). The red curves are Quaternary shortening rate probability density functions (pdf) for the wedge-front Mandeyapecua thrust fault system (Figure 9) based on the analysis presented in Weiss et al [2015]. The pdfs were computed by summing the dip-slip rate pdfs from the profiles shown in Figure 8 of Weiss et al [2015] Profiles 1-5 were summed to create the Sucre profile pdf and profiles 7-8 were summed to create the Tarija profile pdf.…”
Section: Discussion Of Modeling Resultsmentioning
confidence: 99%
“…Most destructive, historic crustal earthquakes in Argentina ( M > 7.0) have been located at the Andean piedmont, between the cities of San Juan and Mendoza (Smalley & Isacks, , ; INPRES, ; Smalley et al, ; Alvarado et al, ; Figure ). The frontal deformation zone of the Andes thus constitutes an area prone to major crustal earthquakes (Brooks et al, ; Costa et al, ; Weiss et al, , ; Yepes et al, ). However, little is known at present about the Andean orogenic front in terms of surficial thrust geometries and rates of Quaternary fault activity.…”
Section: Introductionmentioning
confidence: 99%